2005
DOI: 10.1037/0278-6133.24.4.358
|View full text |Cite
|
Sign up to set email alerts
|

Using UV Photography to Reduce Use of Tanning Booths: A Test of Cognitive Mediation.

Abstract: Two laboratory studies were conducted in which a new type of intervention was used to reduce ultraviolet radiation (UV) exposure from tanning booth use among college students (Time 1 Ns=70 and 134). The intervention uses UV photography to highlight the damage to facial skin caused by previous UV exposure. When the authors controlled for baseline measures of booth use, students in both studies who viewed their UV photographs reported less booth use at a follow-up session 3-4 weeks later than did students not sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
169
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 208 publications
(178 citation statements)
references
References 21 publications
9
169
0
Order By: Relevance
“…The findings to date are quite promising. For example, Gibbons et al (2005) found that Iowa college students who were randomly assigned to view their UV photo reported engaging in less tanning booth use during the following month than those who did not see their UV photo. Mahler et al (2006) also demonstrated that southern California beach patrons who saw their UV facial photo and received information about photoaging (wrinkles and age spots due to UV exposure) engaged in more sun protection behaviors during the subsequent two summer months than did controls.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The findings to date are quite promising. For example, Gibbons et al (2005) found that Iowa college students who were randomly assigned to view their UV photo reported engaging in less tanning booth use during the following month than those who did not see their UV photo. Mahler et al (2006) also demonstrated that southern California beach patrons who saw their UV facial photo and received information about photoaging (wrinkles and age spots due to UV exposure) engaged in more sun protection behaviors during the subsequent two summer months than did controls.…”
mentioning
confidence: 99%
“…Several recent studies have demonstrated the promise of appearance-based interventions, which attempt to motivate sun protection behaviors by highlighting the link between sun exposure and appearance detractors such as wrinkles, age spots, and uneven pigmentation. (Jones & Leary, 1994;Gibbons, Gerrard, Lane, Mahler, & Kulik, 2005;Mahler, Fitzpatrick, Parker, & Lapin, 1997;Mahler, Kulik, Gibbons, Gerrard, & Harrell, 2003;Mahler, Kulik, Harrel, Correa, Gibbons & Gerrard, 2005). Relative to a healthbased message, messages that emphasize negative appearance consequences may better counteract the primary (appearance-based) motivation for sun exposure, namely getting a tan.…”
mentioning
confidence: 99%
“…Interventions to reduce indoor tanning exposure have emphasized prevention or reduction of usage with cessation as an implicit goal [17][18][19][20][21], but little is known about the process by which individuals work towards indoor tanning reduction or cessation, including motivations, facilitators, and barriers to achieving cessation of indoor tanning.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Gibbons and Mahler et al describe a reduction in college students' intention to tan, tanning behavior, and measured skin tan (using a calorimeter) when UV photography was employed. [8,13,16] Most other research has identified that highlighting the connection between UV exposure and its effect on photoaging has given other (often younger) populations another reason to protect themselves from the sun. [10-14, 16, 17] Taken as a whole, these findings suggest that a personalized, interactive approach, with emphasis on high-risk populations, may be an efficacious and valuable approach to skin cancer prevention and awareness in high risk groups.…”
Section: Introductionmentioning
confidence: 99%
“…[8,9] Recent studies have employed UV photography as a personalized, image-based tool that allows for patient interaction and discussion of potential sun exposure risks and counseling regarding sun-protection promotion. [8,[10][11][12][13] A previous study demonstrated that the UV-photography intervention has a greater impact on individuals at higher risk for melanoma. [1,12,14] The immediate results from the UV camera reveal the structural bodily damage characteristic of poor sun protection behavior and may offer a particularly promising approach as the outcomes are often immediately comprehensible to the participant as well as concerning.…”
Section: Introductionmentioning
confidence: 99%